Conceptual instruments for a critical analysis of neoliberalism in Gilles Deleuze’s Thousand Plateaus - Baceiredo, Rebeca (2022)
Along the second volume of Capitalism and schizophrenia, Gilles Deleuze presents a battery of concepts that allow a better understanding of the processes from the economical world and a better analysis of some social logics. Against the critique which accuses him of providing with tools to neoliberalism, his theoretical device can be utilized, indeed, to analyze and disable mimesis between capitalist system and his ontology, because he anticipates in those concepts their impotent issues linked to exercises of power. Power tends to imitate current metaphysic, dealing with mythical theories about the origin of potestas. This article exposes how that mechanism continues existing through capitalist logics of inmanence. For justifying that we recall his epistemology and his ontology, pierced with the notion of difference, to develop the concepts suggested by him in quoted work, so that it shows the rightness to use them in an analysis of this 21th current system. In the same way, some risks of conceptual displacement with an emancipator appearance are presented, already indicated at that time by Deleuze.